2021
DOI: 10.1037/hea0001091
|View full text |Cite
|
Sign up to set email alerts
|

Health-related lifestyle and dropout from a web-based physical activity intervention trial in older adults: A latent profile analysis.

Abstract: Objective: Selective study dropout limits manifestation and detection of intervention effects and is a major challenge in behavioral intervention studies. Engaging in health-risk behaviors might make individuals especially dropout-vulnerable. Thus, this theory-based study's aim was to identify health-related lifestyle profiles affecting dropout in a web-based physical activity intervention trial targeting older adults. Method: The 12week intervention trial was conducted between 2016 and 2018 in Germany. Baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Furthermore, predictors in the linear regression model used here were highly intercorrelated, reducing the interpretability of the impact of the individual intervention elements. Lastly, it is well established that patients with low weight loss are more likely to churn or drop out from treatment over time [ 37 ]. Accordingly, these churned patients will not have contributed data at later time points (e.g., 12 months).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, predictors in the linear regression model used here were highly intercorrelated, reducing the interpretability of the impact of the individual intervention elements. Lastly, it is well established that patients with low weight loss are more likely to churn or drop out from treatment over time [ 37 ]. Accordingly, these churned patients will not have contributed data at later time points (e.g., 12 months).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that web-based and print-based physical activity interventions can increase physical activity in middle-aged and older adults similarly [ 95 , 96 ], suggesting few differences in impact. The recruitment strategy of PROMOTE I and II (mainly targeted active, healthy and science-interested community-dwelling older adults) as well as the systematic dropout in PROMOTE I might also limit the analyzed sample’s representativeness of community-dwelling older adults and should be considered when interpreting the results [ 97 , 98 ]. The recruitment strategy was adapted from PROMOTE I to II because of a physically active and highly educated sample.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to reduce the dropout rate in the WLCG, individuals randomized to this group should be informed about the progress and expected time of participation. As previous studies have indicated that longer waiting times are associated with higher dropout rates, the study design should be adapted to decrease the waiting time for the WLCG [ 8 , 22 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PROMOTE study comprised 2 cohorts: PROMOTE 1 and 2. In this study, web-and print-based programs to promote PA in community-dwelling older adults were developed, analyzed, and evaluated according to multiple theoretical models and intervention effects using randomized intervention trials [49][50][51][52][53][54]. These were conducted as part of the interdisciplinary Physical Activity and Health Equity: Primary Prevention for Healthy Aging research network [55].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation